PENINGKATAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MELALUI MEDIA BOLA PLASTIK PADA MURID SD - M. Imran Hasanuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
This research aims to determine the improvement in learning outcomes of underpassing in volleyball games through the use of plastic balls in class IV students at SD Inpres Kassi. This research is Classroom Action Research (PTK) which consists of two cycles with test and non-test instruments to determine student learning outcomes. The subjects of this research were 24 grade IV students at SD Inpres Kassi. The results of this research show that applying the volleyball underpassing technique using a plastic ball can improve the learning outcomes of volleyball underpassing techniques for fourth grade students at SD Inpres Kassi. This can be seen from the significant increase from cycle I to cycle II. The learning outcomes of the final score in the affective, cognitive and psychomotor aspects in the first cycle of action reached 50%, while in the second cycle of action it reached 87.5%. Based on the research results obtained, it can be concluded that volleyball underpassing using a plastic ball can improve learning outcomes for volleyball underpassing in class IV students at SD Inpres Kassi. Keywords: Bottom Passing, Volleyball, Plastic Ball Media